Assessments of storytelling interpretive panel at heritage site: a case study of visitors’ experience at Dataran Medan Bandar, Alor Setar, Kedah Darul Aman / Wan Iskandar Zulkarnain Wan Shamsuddin and Siti Norlizaiha Harun - Wan Shamsuddin, Wan Iskandar Zulkarnain; Harun, Siti Norlizaiha (Universiti Teknologi MARA, Perak, 2021)
The aim of this study is to find out the existing ‘realities’ on storytelling at heritage sites. The gap is visitor’s expectation between storytelling presentation versus perception of heritage visitors. There were instances in the country whereby misrepresentation and/or inappropriate descriptive information in storytelling has resulted in visitors experiencing disappointment, disorientation, and ignorance of heritage significance. The researchers decided to investigate further on this and had selected a site for case study that was the Dataran Medan Bandar, Alor Setar, Kedah Darul Aman. A sequential mixed methodology was employed. The study began with literature review, site inventory and observation activities in order to obtain qualitative information. This was followed by visitors’ survey and a semi-structured interview with stakeholders to obtain their views on historical and cultural values to validate the quantitative data findings. The explanatory factor analysis was used to analyse the data and the results showed that over 40% of total respondents perceived ‘storytelling’ as extremely important attributes of heritage interpretation during the visit. In terms of the post-experience, the results showed that 18% of the respondents proclaimed of having ‘dissatisfied experience’ after reading the description on interpretive signage, with ‘uninteresting storytelling’ being the main reason. Almost half of total respondents (49%) believe that improvement of ‘Storytelling Content Creation’ was needed at the Dataran Medan Bandar. It is hoped that the findings obtained are expected to inspire conservation stakeholders to start making ‘heritage interpretation’ as a top priority when designing interpretative signs at heritage sites.